Community-based tourism development in Baluran National Park as a sustainable tourism destination - Muhammad Hafif Yadi; Rezki Aulia; Hadi Rudiya; Agus Wiranto (Priviet Social Sciences Journal, 2026)
Tourism is a sector that has grown significantly in recent years after the Covid-19 pandemic. BaluranNational Park is one of the contributors to foreign exchange in the tourism sector in the conservationarea. The increasing potential for visits to Baluran National Park needs to be balanced with thedevelopment of tourist attractions to continue to increase tourist visits and have a greater impact on theeconomy of the surrounding community. This study aims to determine the readiness and preferences ofthe community in order to analyze recommendations for the development of tourist attractions in BaluranNational Park. Data on natural resource potential was collected using observation and literature studymethods. Visitor preference data was collected using a questionnaire method. Community readiness datawas collected using interviews to explore information related to the focus of the study. Baluran NationalPark and the surrounding villages have great potential to support community-based tourism developmentin Baluran National Park. The community is ready to support the development of tourist attractions inBaluran National Park, especially those that will definitely provide maximum benefits and profits withoutdamaging the natural resources in Baluran National Park. The research resulted in two recommendationsfor the development of community-based tourist attractions in Baluran National Park, namely educationaltourism and local cultural tourism. Educational tourism can be developed and conceptualized in line withconservation programs so that natural resources remain preserved. Empowerment that can supporteducational tourism includes handicrafts that depict the culture of the community and the history ofBaluran National Park, as well as innovative and environmentally friendly means of transportation such aselectric vehicles or horse-drawn carriages, which are traditional means of transportation for thecommunity.